Why are IPO investors net buyers through lead underwriters? - Griffin, John M.; Harris, Jeffrey H.; Topaloglu, Selim (Journal of Financial Economics, 2007)
In Nasdaq initial public offerings (IPOs) issued between 1997 and 2002, purchases of lead underwriter clients exceed sales by an amount equal to 8.79% of the total issue. We find that lead underwriter clients do not buy to build larger long-term positions, capitalize on superior execution quality, or because of clientele effects. However, characteristics of net buying that are at odds with these explanations and other behaviors (like institutional purchases of cold IPOs) are all consistent with lead underwriters engaging in quid pro quo arrangements with clients. Price contribution analysis shows that such client buying activity contributes significantly to first-day price increases.